Application of Nanomedicine in Inner Ear Diseases - Lin, Qianyu; Guo, Qiong; Zhu, Mingchao; Zhang, Juanli; Chen, Bei; Wu, Tingting; Jiang, Wei; Tang, Wenxue (Frontiers in Bioengineering and Biotechnology, 2022)
The treatment of inner ear disorders always remains a challenge for researchers. The presence of various physiological barriers, primarily the blood–labyrinth barrier (BLB) limits the accessibility of the inner ear and hinders the efficacy of various drug therapies. Yet despite recent advances in the cochlea for repair and regeneration there are currently no pharmacological or biological interventions for hearing loss. Current research focusses on localized drug, gene and cell-based therapies. Drug delivery based on nanotechnology represents an innovative strategy to improve inner ear treatments. Materials with specific nanostructures not only exhibit unique ability to encapsulate and transport therapeutics to the inner ear, but also endow specific targeting properties to auditory hair cells as well as the stabilization and sustained drug release. Along with this, some alternative route like intratympanic drug delivery can also offer a better means to access the inner ear without exposure of the BLB. This review discusses a variety of nano-based drug delivery systems (DDS) to the ear for treating inner ear diseases. The main factors affecting the curative efficacy of nanomaterials are also discussed. With a deeper understanding of the link between these crucial factors and the clinical effect of nanomaterials, it paves the way for the optimization of the therapeutic activity of nano carriers.